2017
DOI: 10.3221/igf-esis.42.33
|View full text |Cite
|
Sign up to set email alerts
|

Strain capacity assessment of API X65 steel using damage mechanics

Abstract: International audienceStrain-based design for offshore pipeline requires a considerable experimental work aimed to determine the material fracture toughness and the effective strain capacity of pipe and welds. Continuum damage mechanics can be used to limit the experimental effort and to perform most of the assessment analysis and evaluation in a simulation environment. In this work, the possibility to predict accurately fracture resistance of X65 steel using a CDM model proposed by the authors, is shown. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…ipelines are very important tool to transport hydrocarbons with high safety properties over long distances [1][2][3]. Indeed, the piping systems including the elbows are subjected to severe factors which may menace the integrity and safety of the pipe [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…ipelines are very important tool to transport hydrocarbons with high safety properties over long distances [1][2][3]. Indeed, the piping systems including the elbows are subjected to severe factors which may menace the integrity and safety of the pipe [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Det Norske Veritas (DNV) (Submarine pipeline systems) advised using damage models to simulate crack growth for the design of submarine pipelines. Testa et al (2017), proposed a continuum damage mechanics (CDM) model to predict the strain capacity of X65 steel, which performed well in predicting ductile crack growth of single-edge notched bending (SENB) and SENT fracture specimens. The Gurson-Tvegaar-Needleman (GTN) model has been the method most often used to simulate the ductile fracture process consisting of nucleation, growth, and coalescence of microvoids (Zhu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that other factors may influence the decrease in fatigue resistance of the corroded connection, such as a variation in the slip coefficient between plates or a certain amount of loss of bolts pretension, which may resulted in a decrease in the friction resistance of the connection and consequently a bearing type behaviour of it [4]. Based on Continuum damage mechanics (CDM), Gabriel Testa et al [5] have used the Bonora damage model (BDM) to predict the strain limit capacity of X65 steel grade used for pipeline application. it was shown that numerical simulation with CDM could be used to carry on "virtual experiments" for the determination of the material fracture toughness with high degree of accuracy.…”
Section: Introductionmentioning
confidence: 99%